Urban occupation increases water toxicity of an important river in central Brazil - Cardoso Bailão, Elisa Flávia Luiz; Sousa Zago, Leciana de Menezes; Silva, Nathan Carvalho; Machado, Karine Borges; D’Abadia, Patrícia Lima; Francisco de Oliveira, Pedro Henrique; Nabout, João Carlos; Madureira de Almeida, Luciane [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
Meia Ponte River supplies water for two million people in Goiás State, Brazil. Despite its importance, the Meia Ponte River faces serious environmental problems such as the disposal of domestic and industrial effluents, what could impact the aquatic biota and the health of people who consumes its water. In this sense, here we aimed to evaluate the environmental quality and toxicity of surface water along the course of this river. Physicochemical analyses of water at Goiânia urban perimeter were higher than the limits of Brazil environmental regulations for fresh water. In relation to the diversity of species, phytoplankton classes associated to polluted environments were detected closer to urban perimeter. Allium cepa bioassay suggested that this river may contain substances with mitogenic activity. This result is in accordance with genotoxic analysis, because it was observed a significant increase in chromosomal aberrations. This data reveal the genotoxic potential of Meia Ponte River water. This genotoxicity represents a risk for aquatic biota and humans, once the genotoxic agents in water samples might cause the loss of DNA integrity, inducing damages and DNA breaks. In this context, the water utilization from Meia Ponte River without any treatment should be avoided and public policies need to be formulated and implemented to depollute this important river for Goiás State.
Ocupação urbana aumenta a toxicidade da água de um importante Rio no Brasil central
Keywords: Chromosomal Aberrations; Cytogenotoxicity; Meia Ponte River; Phytoplankton